Mapping Idiomatic Morphology of Nusantara Mosques - Md. Sharif, Harlina (2019)
Islam, that arrived in Nusantara in the 11th century (if not earlier) and formed its earliest centers in Pasai-Samudera and Lamuri, brought with its call (da’wah) the idea of ummah i.e the bond of universal brotherhood. This concept, when translated liturgically and architecturally, takes the form of a structure, a purposely designed communal center. Masjid or Mosque as we know it today, absorbs the intent of the Syari’ (the Law-Giver) and deciphered into the aspirations of the people, reflecting peculiar idioms of its time and region, and exhibiting local taste and technology. In the same spirit of how Islam came to the Nusantara, the mosque’s design evolved following the rhythms of the community. This organic evolution of Islamic-Nusantara idiomatic idiosyncrasies however was abruptly truncated at the dawn of Colonialism, especially with the arrival of Dutch and British to the region in the 17th and 18th century. This seminar looks into the forms and the artistic traditions of Nusantara mosques and what they meant to the Nusantara Muslims of that era. It concludes with questions on identity, symbolic meanings and the ideal design of a mosque that represents the soul, the aspirations and the technology available today.